Managing inter-organizational conflict: Efficient interaction strategies for buyer and seller organization - Hans Georg Gemünden (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1981)
The transaotion of a oomplex innovative oapital good between a seller and a buyer Organization is seen as a oomplex task being oomposed of two important subtasks: the development of a problem Solution whioh is to be implemented into the buyer Organisation, and the management of inter-organizational oonfliot. In this paper the author analyses how both parties oan manage their inter-organizational oonfliots and whioh effioienoy effeots will result when they dhoose a oertain inter-aation strategy. A general effioienoy hypothesis is deduoted proposing a D-shaped relation between oonfliot handling in-tensity and buyer's and seller's effioienoy. More preoisely two H -shaped relation are developed3 stating that the seller will reach its maximum effioienoy at a quite low level of oonfliot handling intensity whereas the buyer will reaoh its maximum effioienoy at a quite high level of oonfliot handling intensity. To test this hypothesis empirioally a oonaept to measure the transaotional effioienoy of buyer and seller Organization and a typology of oonfliot handling interaotion stra-tegies are developed and applioated to 195 transaotion prooesses where eomputers were bought or leased for the first time.
Keywords: 650